From the Internal Market to the citizenship of rights: the protection of personal data as the jus-fundamental identity question of our times - Silveira, Alessandra (2018)
Bearing in mind the applicability of the General Data Protection Regulation as of May 25, 2018, the Authors use the teachings of computer engineers to explain the extent to which data (including personal data) is at the basis of the algorithmic revolution that is reconfiguring science, business, and politics. The Authors argue that, in the context of the European Union’s assertion as a Union based on the rule of law, the importance and attention given to the effectiveness of the fundamental right to the protection of personal data is justified not only by the pressure of the technological times we are experiencing and by the gradual emergence of a homo digitalis. At the same time, the increasingly (outspokenly) political sense of deepening integration, as well as the priority placed on building European citizenship and reinforcing a dimension of extraeconomic integration, all contribute to the development of a European fundamental rights culture. The referential paradigm of the Internal Market is, nowadays, a market where, first and foremost, citizens are moving and circulating, who are also circumstantially, economic agents and consumers. In this sense, the Authors seek to demonstrate why the protection of personal data has become the jus-fundamental identity issue of our times, basically so that the project of humanism does not become irrelevant.